An Efficient, Multi‐element AC/TiO2/WO3 Photocatalyst for the Degradation of Tetracycline Hydrochloride. Issue 8 (21st February 2022) - Xu, Mengdi; Nan, Hui; Yang, Hao; Xue, Caihong; Fu, Hua; Yang, Guijun; Chen, Huiyuan; Lin, Hong
Abstract: In this study, a simple one‐step hydrothermal synthesis of three‐element complex system photocatalyst technology is systematically studied. The results show that due to the complex heterojunction formed by titanium dioxide (TiO2 ), tungsten trioxide (WO3 ) and activated carbon (AC) and the strong adsorption performance of AC, the catalytic efficiency and cycle stability of the composite have been significantly improved. The excellent electron transport ability of AC is conducive to the separation of carriers, so that the electron transfer between AC/TiO2 and AC/WO3 can make it achieve a heterojunction effect similar to TiO2 /WO3 . The rich specific surface area of AC and the pores of the "labyrinth" structure can provide a higher concentration of degradable substances inside the catalyst, and the degraded substances are quickly transferred to the active site for degradation. Therefore, by controlling the mass ratio of AC/TiO2 /WO3, a photocatalyst with high catalytic efficiency and strong cycle stability was successfully prepared (the degradation efficiency is above 95 %, and the degradation efficiency after 5 cycles is above 80 %). Abstract : A simple one‐step hydrothermal synthesis of three‐element complex system photocatalyst technology is systematically studied. The results show that due to the complex heterojunction formed by titanium dioxide (TiO2 ), tungsten trioxide (WO3 ) and activated carbon (AC) and the strong adsorption performance of AC, the catalytic efficiency and cycle stability of the composite have been significantly improved. The multi‐element coordinated supported photocatalyst is an effective and promising photocatalyst, which provides a new idea for the development of the catalysis field.